Psycho-motor development: variability, disturbances and learning difficulties (Portuguese Journal of Family Medicine and General Practice, 2004)
Whenever we see, hear, learn or simply remember anything, however small, there is modification of brain circuits, this ability to change, plastic, from experience, is crucial for the proper functioning of the whole.